Evaluating the immunogenicity of chemically-synthesised peptides derived from foot-and-mouth disease VP1, VP2 and VP3 proteins as vaccine candidates (2020)
Foot-and-mouth disease (FMD) is one of the most contagious veterinary viral diseases known, having economic, social and potentially devastating environmental impacts. The vaccines currently being marketed/sold around the world for disease control and prevention in bovines do not stimulate the production of antibodies having crossed reactions to different serotypes. This means that if an animal becomes infected by a serotype which has not been included in a vaccine then it will develop the disease. Synthetic peptide vaccines represent a safer option and (depending on the design) can stimulate antibodies protecting against different variants. Based on the forgoing, this work was aimed at evaluating FMDV VP1, VP2 and VP3 protein-derived, modified and chemically-synthesised peptides’ ability to induce an immune response for developing a vaccine contributing towards controlling the disease. VP1, VP2 and VP3 proteins’ conserved regions were selected for this. Peptides from these regions were chemically synthesised; binding assays were then carried out for ascertaining whether they were involved in BHK-21 cell binding. Selected peptides’ structure and location were studied. Peptides which did bind were modified and formulated with Montanide ISA 70 adjuvant; 17 animals were immunised twice with the formulation. The animals were genotyped by amplifying the BoLA-DRB3.2 gene. Blood samples were taken from 17 cattle on day 43 post-first immunisation for studying the formulation's immunogenicity. The sera were used in ELISA, immunofluorescence, flow cytometry, immunoadsorption and seroneutralisation assays. The A24 Cruzeiro and O1 Campos virus serotypes were used for these assays. The results revealed that even though protein exposure and 3D structure might be different amongst serotypes, the antibodies so produced could inhibit virus entry to cells, thereby showing the selected peptides’ in vitro protection-inducing ability. © 2020 Elsevier Ltd